Analisis Kebutuhan Penerima Manfaat Penyuluhan Sastra di Kabupaten Jayapura, Provinsi Papua: Analysis of The Needs of Beneficiaries of Literary Counseling in Jayapura District, Papua Province - Lestari, Ummu Fatimah Ria (Balai Bahasa Provinsi Papua, 2023)
One of the UPT Badan Bahasa in Papua, Balai Bahasa Provinsi Papua has also conducted literature counseling in various forms so far. The diversity in the implementation of literature counseling by Balai Bahasa Provinsi Papua in Papua is the background to this research. Based on the background previously stated, this research will focus on the needs of beneficiaries of literature counseling in Jayapura Regency. This study aims to formulate the design and construction of literary extension so that it can be carried out in a structured and well-planned manner. In particular, this study aims to analyze the needs of beneficiaries of literary counseling. This research was conducted using a quantitative description approach. In addition to the results of a questionnaire, the data in the study were also supplemented by observations, document scrutiny, and unstructured interviews. Respondents in this study totaled thirty people consisting of students, teachers, university students, and the general public in Jayapura Regency, Papua Province. The needs of the beneficiaries of literary counseling in Jayapura Regency are related to services and literary counseling, the activities of participants in literary counseling, and the environment for literary counseling.